Stakeholder perspectives on general competences: The case of graduates of Vietnam National University, Hanoi - Lan Thi Quynh Mai (Universidad de Deusto, 2020)
This research draws from theories of graduate employability and transferable skills and the TASE project's 13 graduate competences model, to explore the evaluation of the various stakeholders concerning the degree to which VNU graduates have acquired general competences. The survey measured three variables: (i) importance, (ii) achievement and (iii) priority, using the four categories of 'none', 'weak', 'considerable', and 'strong'. Between February and December 2018, a total of 818 informants agreed to participate, including 168 employers, 152 alumni, 189 students who had just graduated in 2018 or were about to graduate, 51 lecturers and university managers, and 258 students. The importance of the 13 general competences was rated more highly than graduate achievement. The ability to uphold professional, moral and ethical values was rated by VNU employers as of greatest importance and the highest achievement. Similarly, VNU students and alumni rated this ability as their highest achievement. The ability to conduct research and the ability to understand, value, and respect diversity and multiculturalism were rated as of lowest importance by VNU employers. The former (ability to conduct research) was rated as of lowest importance by VNU alumni and their lowest achievement by both VNU alumni and VNU students. VNU students rated the latter ability (to understand, value, and respect diversity and multiculturalism) as of least importance. The ability to initiate, plan, organise, implement and evaluate courses of action was rated the lowest achievement by VNU employers. The ability to apply knowledge in practice was considered of greatest importance by both VNU students and alumni, but for the latter group this ability ranked equally with the ability to communicate clearly and effectively. Students gave most of their own general competences a significantly lower rating than that given by employers to alumni achievement. Received: 26 June 2019 Accepted: 13 March 2020 Published online: 19 May 2020